ANALISIS PEMAHAMAN MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS JEMBER TERKAIT TEKNIK IRRADIASI SINAR GAMMA PADA PENGAWETAN MAKANAN - Kasanah, Nur; Chandhani, Erika Divian; Prabandari, Audri Mely; Sudarti, Sudarti; Prihandono, Trapsilo (JURNAL PEMBELAJARAN FISIKA, 2023)
One of the materials studied by physics education students at the University of Jember in the agrophysics course is material about ionizing and non-ionizing radiation. Understanding the material requires the ability to think critically. With critical thinking, students' understanding can be said to be good on ionizing and non-ionizing radiation material. In this study using descriptive research methods with a quantitative approach. The purpose of using this method is to describe the understanding of physics education students in understanding ionizing radiation material (ionizing) type of gamma rays on food preservation. Respondents in this study were physics education students at the University of Jember totaling 50 students. Data were collected by distributing questionnaires. Based on the results of the analysis of the answers obtained from the Physics Education students of Jember University on the questionnaire regarding the understanding of gamma-ray irradiation techniques in food preservation, it can be concluded that the understanding of the concept of students is quite good. Students who are prospective physics teachers must have an understanding of the concept of physics. To improve understanding, it is necessary to have a good discussion and argue logically to train critical thinking.